2023
DOI: 10.3390/v15020578
|View full text |Cite
|
Sign up to set email alerts
|

Human Coronavirus OC43 as a Low-Risk Model to Study COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had irreversible and devastating impacts on every aspect of human life. To better prepare for the next similar pandemic, a clear understanding of coronavirus biology is a prerequisite. Nevertheless, the high-risk nature of the causative agent of COVID-19, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), requires the use of a cumbersome biosafety level-3 (BSL-3) confinement facility. To facilitate the development of preventive and therapeutic mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 147 publications
0
18
0
Order By: Relevance
“…In summary, it is known that the root cause of Long COVID-associated OD is persistent viral presence (persistent infection), inflammation of olfactory epithelia, and apoptosis of the epithelial/neuronal cells [ 4 ]. The results of the current study demonstrated that EC16/EC16m in the saline-based nanoformulations was able to rapidly inactivate β-coronavirus OC43, the strain with high genome homology with SARS-CoV-2 [ 28 ] by direct contact (1 min), and to reduce cytopathic effect after a post-infection treatment (10 min). With the known anti-inflammatory, antioxidant, and neuroprotective properties, intranasally delivered EC16m could potentially not only terminate the “persistent infection” in the OE, but also inhibit local inflammation and apoptosis, thereby normalizing the olfactory function and inhibit inflammation in the CNS.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, it is known that the root cause of Long COVID-associated OD is persistent viral presence (persistent infection), inflammation of olfactory epithelia, and apoptosis of the epithelial/neuronal cells [ 4 ]. The results of the current study demonstrated that EC16/EC16m in the saline-based nanoformulations was able to rapidly inactivate β-coronavirus OC43, the strain with high genome homology with SARS-CoV-2 [ 28 ] by direct contact (1 min), and to reduce cytopathic effect after a post-infection treatment (10 min). With the known anti-inflammatory, antioxidant, and neuroprotective properties, intranasally delivered EC16m could potentially not only terminate the “persistent infection” in the OE, but also inhibit local inflammation and apoptosis, thereby normalizing the olfactory function and inhibit inflammation in the CNS.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, the results of the current study demonstrated that the saline-based EC16m mucoadhesive nasal Formulation D is highly effective against human β-coronavirus OC43, the strain with high genome homology with SARS-CoV-2 (45), and in reducing viral replication after a single 5-min post-infection treatment, without mucociliary toxicity. With the known anti-inflammatory, antioxidant, and neuroprotective properties, intranasally delivered EC16m by Formulation D could not only terminate the "persistent infection" in the olfactory epithelium, but also inhibit local inflammation and apoptosis, thereby restore the olfactory function and reduce free radical levels and inflammation in the CNS.…”
Section: Discussionmentioning
confidence: 62%
“…Cross-reactive T-cell epitopes have also been identi ed between SARS-CoV-2, HCoVs, and live attenuated vaccines (LAVs), further emphasizing the potential for pre-existing immunity to in uence COVID-19 outcomes 14 . This is due to their closeness in their molecular structures 15 . Analysis of known epitope sequences from SARS-CoV, SARS-CoV-2, and other Coronaviridae has revealed conserved epitopes between SARS-CoV-2 and SARS-CoV, particularly in the nucleoprotein and spike glycoprotein, suggesting shared antigenic sites that could be targeted for vaccine development 16,17 .…”
Section: Introductionmentioning
confidence: 97%